The mammal list of Muong Phong area, Phu Yen district, Son La province - Hai, Tran Hong; Viet, Tran Hong; Canh, Le Xuan; Dang, Nguyen Xuan (Academia Journal of Biology, 2012)
Based on the relevant published documents, results of mammal fauna surveys in many years in 4 communes of Phu Yen district, Son La province which called Muong Phong area and 190 collected specimens the authors have proposed a mammals list of Muong Phong area consist of 116 species and subspecies belonging to 74 genus, 27 families, 9 orders existing mammals in Vietnam with their vernacular names. Among 112 species of mammals in Muong Phong 8 species (occupied 7.33% of species) is already extinted, 24 species (20.69%) are rare and 54 species (46.55%) with small population number. From the list, we know that about 74.14% of the species are under medium level of copiousness and if we don’t have urgent measures for protection of mammals species in the area or establishing new conservation area as Muong Phong, in PhuYen district, SonLa province many mammals species will be loosed locally in near future.